The Test Bench for Simulation Phase Fault and Ground Fault Analysis Protection Concept Using Symmetrical Components - Supriyanto, Supriyanto; Utomo, Heri Budi; Sunarto, Sunarto; Siswoyo, Siswoyo; Setiadi, Budi (Bandung State Polytechnic (Politeknik Negeri Bandung), 2023)
Various laboratory experiment platforms have been developed to provide students with theoretical knowledge and practical experience. Understanding concepts related to the process for determining the design of protection settings requires practical experience, which can be achieved by repeated trials. In this paper, the mechanism of a ground fault in a medium voltage feeder is done using a simulator substation as a case study. This process must be carried out twice, once for the ground-fault relays protection based on residual currents and then repeated based on residual voltage. For further understanding of the electrical distribution network, the system will be operated at 20 kV on the primary and 380 V on the secondary. The model uses smaller nominal voltages consisting of 380 V on the primary and the secondary. The result of one phase fault protection mechanism works well at each point of interference, and voltage transformers are protected from overheating and damage. The lowest value of the single-phase to ground short circuit that occurs at the fault location at the farthest point of interference from the protection relay location is used for the threshold setting on the voltage relay. The one phase fault protection mechanism works well at each point of interference, and the voltage transformer is protected from overheating and damage. For residual current ground fault protection effective, the threshold setting of phase fault inverse time delay with threshold setting I> is 1.5 ampere, and instantaneous I>> is 7.5 ampere. The effective threshold setting for residual ground fault protection wasUo> = 22% dan UO>> = 33,2%.